2020
DOI: 10.1103/physreva.101.013820
|View full text |Cite
|
Sign up to set email alerts
|

Ghost imaging at an XUV free-electron laser

Abstract: Radiation damage is one of the most severe resolution limiting factors in x-ray imaging, especially relevant to biological samples. One way of circumventing this problem is to exploit correlationbased methods developed in quantum imaging. Among these, there is ghost imaging (GI) in which the image is formed by radiation that has never interacted with the sample. Here, we demonstrate GI at an XUV free-electron laser by utilizing correlation techniques. We discuss the experimental challenges, optimal setup, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Can multiplex sensing enable one to obtain more information for a given radiation dose? Many atomic resolution imaging tasks are radiation-damage limited, and the possibility to use multiplex sensing to overcome that limit has been discussed in recent literature [3][4][5]7]. This discussion has revolved around ghost imaging setups, where it has been suggested that damage might be avoided by decreasing the flux on the object branch and increasing the flux into the reference branch.…”
Section: Signal-to-noise Per Dosementioning
confidence: 99%
See 2 more Smart Citations
“…Can multiplex sensing enable one to obtain more information for a given radiation dose? Many atomic resolution imaging tasks are radiation-damage limited, and the possibility to use multiplex sensing to overcome that limit has been discussed in recent literature [3][4][5]7]. This discussion has revolved around ghost imaging setups, where it has been suggested that damage might be avoided by decreasing the flux on the object branch and increasing the flux into the reference branch.…”
Section: Signal-to-noise Per Dosementioning
confidence: 99%
“…There has been recent interest in the use of multiplex sensing techniques in applications at the atomic scale [1][2][3][4][5][6][7][8]. Traditionally, measurements using x-rays or electrons systematically interrogate a system at a single point in space, time, or photon/electron energy at once before moving on to the next measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray ghost imaging has now been demonstrated multiple times [10][11][12][13][14][15][16][17]; however, it is still a developing field. One commonly used technique for current X-ray ghost imaging is to introduce a spatially varied material to produce a "speckle" pattern in the X-ray beam.…”
Section: Introductionmentioning
confidence: 99%
“…Pelliccia et al use type (I) ghost imaging in their first demonstration of X-ray ghost imaging [11]. Alternatively, (II) the observed ghost image is produced from a classical speckle-to-speckle correlation shown with visible light [21][22][23] and with a variety of X-ray sources [12,[14][15][16][17]. Here, a ghost image of the object is obtained from the coincidences between two sets of identical "speckles" formed by either spatially correlated laser beams or an aperture mask following the light source to produce shadows and bright spots distributed on the object plane and on the ghost image (detector) plane.…”
Section: Introductionmentioning
confidence: 99%